Multiple loci influence erythrocyte phenotypes in the CHARGE Consortium. - Ganesh, Santhi K; Zakai, Neil A; van Rooij, Frank J A; Soranzo, Nicole; Smith, Albert V; Nalls, Michael A; Chen, Ming-Huei; Köttgen, Anna; Glazer, Nicole L; Dehghan, Abbas; Kuhnel, Brigitte; Aspelund, Thor; et al. (Nat Genet, 2009)
Measurements of erythrocytes within the blood are important clinical traits and can indicate various hematological disorders. We report here genome-wide association studies (GWAS) for six erythrocyte traits, including hemoglobin concentration (Hb), hematocrit (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and red blood cell count (RBC). We performed an initial GWAS in cohorts of the CHARGE Consortium totaling 24,167 individuals of European ancestry and replication in additional independent cohorts of the HaemGen Consortium totaling 9,456 individuals. We identified 23 loci significantly associated with these traits in a meta-analysis of the discovery and replication cohorts (combined P values ranging from 5 x 10(-8) to 7 x 10(-86)). Our findings include loci previously associated with these traits (HBS1L-MYB, HFE, TMPRSS6, TFR2, SPTA1) as well as new associations (EPO, TFRC, SH2B3 and 15 other loci). This study has identified new determinants of erythrocyte traits, offering insight into common variants underlying variation in erythrocyte measures.
Keywords: Blood Pressure; Cell Line; Cohort Studies; Endothelial Cells; Erythrocytes; Gene Expression; Genome, Human; Genome-Wide Association Study; Humans; Hypertension; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Association analyses of 249,796 individuals reveal 18 new loci associated with body mass index. - Speliotes, Elizabeth K; Willer, Cristen J; Berndt, Sonja I; Monda, Keri L; Thorleifsson, Gudmar; Jackson, Anne U; Lango Allen, Hana; Lindgren, Cecilia M; Luan, Jian'an; Mägi, Reedik; Randall, Joshua C; Vedantam, Sailaja; et al. (Nat Genet, 2010)
Obesity is globally prevalent and highly heritable, but its underlying genetic factors remain largely elusive. To identify genetic loci for obesity susceptibility, we examined associations between body mass index and ∼ 2.8 million SNPs in up to 123,865 individuals with targeted follow up of 42 SNPs in up to 125,931 additional individuals. We confirmed 14 known obesity susceptibility loci and identified 18 new loci associated with body mass index (P < 5 × 10⁻⁸), one of which includes a copy number variant near GPRC5B. Some loci (at MC4R, POMC, SH2B1 and BDNF) map near key hypothalamic regulators of energy balance, and one of these loci is near GIPR, an incretin receptor. Furthermore, genes in other newly associated loci may provide new insights into human body weight regulation.
Keywords: Body Height; Body Mass Index; Body Size; Body Weight; Chromosome Mapping; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Obesity; Polymorphism, Single Nucleotide

Biological, clinical and population relevance of 95 loci for blood lipids. - Teslovich, Tanya M; Musunuru, Kiran; Smith, Albert V; Edmondson, Andrew C; Stylianou, Ioannis M; Koseki, Masahiro; Pirruccello, James P; Ripatti, Samuli; Chasman, Daniel I; Willer, Cristen J; Johansen, Christopher T; Fouchier, Sigrid W; et al. (Nature, 2010)
Plasma concentrations of total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides are among the most important risk factors for coronary artery disease (CAD) and are targets for therapeutic intervention. We screened the genome for common variants associated with plasma lipids in >100,000 individuals of European ancestry. Here we report 95 significantly associated loci (P < 5 x 10(-8)), with 59 showing genome-wide significant association with lipid traits for the first time. The newly reported associations include single nucleotide polymorphisms (SNPs) near known lipid regulators (for example, CYP7A1, NPC1L1 and SCARB1) as well as in scores of loci not previously implicated in lipoprotein metabolism. The 95 loci contribute not only to normal variation in lipid traits but also to extreme lipid phenotypes and have an impact on lipid traits in three non-European populations (East Asians, South Asians and African Americans). Our results identify several novel loci associated with plasma lipids that are also associated with CAD. Finally, we validated three of the novel genes-GALNT2, PPP1R3B and TTC39B-with experiments in mouse models. Taken together, our findings provide the foundation to develop a broader biological understanding of lipoprotein metabolism and to identify new therapeutic opportunities for the prevention of CAD.
Keywords: African Americans; Animals; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Europe; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Lipid Metabolism; Lipids; Liver; Male; Mice; N-Acetylgalactosaminyltransferases; Phenotype; Polymorphism, Single Nucleotide; Protein Phosphatase 1; Reproducibility of Results; Triglycerides

Common genetic determinants of vitamin D insufficiency: a genome-wide association study. - Wang, Thomas J; Zhang, Feng; Richards, J Brent; Kestenbaum, Bryan; van Meurs, Joyce B; Berry, Diane; Kiel, Douglas P; Streeten, Elizabeth A; Ohlsson, Claes; Koller, Daniel L; Peltonen, Leena; Cooper, Jason D; et al. (Lancet, 2010)
BACKGROUND: Vitamin D is crucial for maintenance of musculoskeletal health, and might also have a role in extraskeletal tissues. Determinants of circulating 25-hydroxyvitamin D concentrations include sun exposure and diet, but high heritability suggests that genetic factors could also play a part. We aimed to identify common genetic variants affecting vitamin D concentrations and risk of insufficiency. METHODS: We undertook a genome-wide association study of 25-hydroxyvitamin D concentrations in 33 996 individuals of European descent from 15 cohorts. Five epidemiological cohorts were designated as discovery cohorts (n=16 125), five as in-silico replication cohorts (n=9367), and five as de-novo replication cohorts (n=8504). 25-hydroxyvitamin D concentrations were measured by radioimmunoassay, chemiluminescent assay, ELISA, or mass spectrometry. Vitamin D insufficiency was defined as concentrations lower than 75 nmol/L or 50 nmol/L. We combined results of genome-wide analyses across cohorts using Z-score-weighted meta-analysis. Genotype scores were constructed for confirmed variants. FINDINGS: Variants at three loci reached genome-wide significance in discovery cohorts for association with 25-hydroxyvitamin D concentrations, and were confirmed in replication cohorts: 4p12 (overall p=1.9x10(-109) for rs2282679, in GC); 11q12 (p=2.1x10(-27) for rs12785878, near DHCR7); and 11p15 (p=3.3x10(-20) for rs10741657, near CYP2R1). Variants at an additional locus (20q13, CYP24A1) were genome-wide significant in the pooled sample (p=6.0x10(-10) for rs6013897). Participants with a genotype score (combining the three confirmed variants) in the highest quartile were at increased risk of having 25-hydroxyvitamin D concentrations lower than 75 nmol/L (OR 2.47, 95% CI 2.20-2.78, p=2.3x10(-48)) or lower than 50 nmol/L (1.92, 1.70-2.16, p=1.0x10(-26)) compared with those in the lowest quartile. INTERPRETATION: Variants near genes involved in cholesterol synthesis, hydroxylation, and vitamin D transport affect vitamin D status. Genetic variation at these loci identifies individuals who have substantially raised risk of vitamin D insufficiency. FUNDING: Full funding sources listed at end of paper (see Acknowledgments).
Keywords: Canada; Chromosomes, Human, Pair 11; Chromosomes, Human, Pair 4; Cohort Studies; Dietary Supplements; Europe; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Homozygote; Humans; Immunoassay; International Cooperation; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Seasons; United States; Vitamin D; Vitamin D Deficiency

Genome-wide association identifies OBFC1 as a locus involved in human leukocyte telomere biology. - Levy, Daniel; Neuhausen, Susan L; Hunt, Steven C; Kimura, Masayuki; Hwang, Shih-Jen; Chen, Wei; Bis, Joshua C; Fitzpatrick, Annette L; Smith, Erin; Johnson, Andrew D; Gardner, Jeffrey P; Srinivasan, Sathanur R; et al. (Proc Natl Acad Sci U S A, 2010)
Telomeres are engaged in a host of cellular functions, and their length is regulated by multiple genes. Telomere shortening, in the course of somatic cell replication, ultimately leads to replicative senescence. In humans, rare mutations in genes that regulate telomere length have been identified in monogenic diseases such as dyskeratosis congenita and idiopathic pulmonary fibrosis, which are associated with shortened leukocyte telomere length (LTL) and increased risk for aplastic anemia. Shortened LTL is observed in a host of aging-related complex genetic diseases and is associated with diminished survival in the elderly. We report results of a genome-wide association study of LTL in a consortium of four observational studies (n = 3,417 participants with LTL and genome-wide genotyping). SNPs in the regions of the oligonucleotide/oligosaccharide-binding folds containing one gene (OBFC1; rs4387287; P = 3.9 x 10(-9)) and chemokine (C-X-C motif) receptor 4 gene (CXCR4; rs4452212; P = 2.9 x 10(-8)) were associated with LTL at a genome-wide significance level (P < 5 x 10(-8)). We attempted replication of the top SNPs at these loci through de novo genotyping of 1,893 additional individuals and in silico lookup in another observational study (n = 2,876), and we confirmed the association findings for OBFC1 but not CXCR4. In addition, we confirmed the telomerase RNA component (TERC) as a gene associated with LTL (P = 1.1 x 10(-5)). The identification of OBFC1 through genome-wide association as a locus for interindividual variation in LTL in the general population advances the understanding of telomere biology in humans and may provide insights into aging-related disorders linked to altered LTL dynamics.
Keywords: Cohort Studies; Genome-Wide Association Study; Genotype; Humans; Leukocytes; Polymorphism, Single Nucleotide; Receptors, CXCR4; Telomere; Telomere-Binding Proteins

Hundreds of variants clustered in genomic loci and biological pathways affect human height. - Lango Allen, Hana; Estrada, Karol; Lettre, Guillaume; Berndt, Sonja I; Weedon, Michael N; Rivadeneira, Fernando; Willer, Cristen J; Jackson, Anne U; Vedantam, Sailaja; Raychaudhuri, Soumya; Ferreira, Teresa; Wood, Andrew R; et al. (Nature, 2010)
Most common human traits and diseases have a polygenic pattern of inheritance: DNA sequence variants at many genetic loci influence the phenotype. Genome-wide association (GWA) studies have identified more than 600 variants associated with human traits, but these typically explain small fractions of phenotypic variation, raising questions about the use of further studies. Here, using 183,727 individuals, we show that hundreds of genetic variants, in at least 180 loci, influence adult height, a highly heritable and classic polygenic trait. The large number of loci reveals patterns with important implications for genetic studies of common human diseases and traits. First, the 180 loci are not random, but instead are enriched for genes that are connected in biological pathways (P = 0.016) and that underlie skeletal growth defects (P < 0.001). Second, the likely causal gene is often located near the most strongly associated variant: in 13 of 21 loci containing a known skeletal growth gene, that gene was closest to the associated variant. Third, at least 19 loci have multiple independently associated variants, suggesting that allelic heterogeneity is a frequent feature of polygenic traits, that comprehensive explorations of already-discovered loci should discover additional variants and that an appreciable fraction of associated loci may have been identified. Fourth, associated variants are enriched for likely functional effects on genes, being over-represented among variants that alter amino-acid structure of proteins and expression levels of nearby genes. Our data explain approximately 10% of the phenotypic variation in height, and we estimate that unidentified common variants of similar effect sizes would increase this figure to approximately 16% of phenotypic variation (approximately 20% of heritable variation). Although additional approaches are needed to dissect the genetic architecture of polygenic human traits fully, our findings indicate that GWA studies can identify large numbers of loci that implicate biologically relevant genes and pathways.
Keywords: Body Height; Chromosomes, Human, Pair 3; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Metabolic Networks and Pathways; Multifactorial Inheritance; Phenotype; Polymorphism, Single Nucleotide

Meta-analysis identifies 13 new loci associated with waist-hip ratio and reveals sexual dimorphism in the genetic basis of fat distribution. - Heid, Iris M; Jackson, Anne U; Randall, Joshua C; Winkler, Thomas W; Qi, Lu; Steinthorsdottir, Valgerdur; Thorleifsson, Gudmar; Zillikens, M Carola; Speliotes, Elizabeth K; Mägi, Reedik; Workalemahu, Tsegaselassie; White, Charles C; et al. (Nat Genet, 2010)
Waist-hip ratio (WHR) is a measure of body fat distribution and a predictor of metabolic consequences independent of overall adiposity. WHR is heritable, but few genetic variants influencing this trait have been identified. We conducted a meta-analysis of 32 genome-wide association studies for WHR adjusted for body mass index (comprising up to 77,167 participants), following up 16 loci in an additional 29 studies (comprising up to 113,636 subjects). We identified 13 new loci in or near RSPO3, VEGFA, TBX15-WARS2, NFE2L3, GRB14, DNM3-PIGC, ITPR2-SSPN, LY86, HOXC13, ADAMTS9, ZNRF3-KREMEN1, NISCH-STAB1 and CPEB4 (P = 1.9 × 10⁻⁹ to P = 1.8 × 10⁻⁴⁰) and the known signal at LYPLAL1. Seven of these loci exhibited marked sexual dimorphism, all with a stronger effect on WHR in women than men (P for sex difference = 1.9 × 10⁻³ to P = 1.2 × 10⁻¹³). These findings provide evidence for multiple loci that modulate body fat distribution independent of overall adiposity and reveal strong gene-by-sex interactions.
Keywords: Adipose Tissue; Age Factors; Chromosome Mapping; Female; Genome, Human; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Sex Characteristics; Waist-Hip Ratio

New genetic loci implicated in fasting glucose homeostasis and their impact on type 2 diabetes risk. - Dupuis, Josée; Langenberg, Claudia; Prokopenko, Inga; Saxena, Richa; Soranzo, Nicole; Jackson, Anne U; Wheeler, Eleanor; Glazer, Nicole L; Bouatia-Naji, Nabila; Gloyn, Anna L; Lindgren, Cecilia M; Mägi, Reedik; et al. (Nat Genet, 2010)
Levels of circulating glucose are tightly regulated. To identify new loci influencing glycemic traits, we performed meta-analyses of 21 genome-wide association studies informative for fasting glucose, fasting insulin and indices of beta-cell function (HOMA-B) and insulin resistance (HOMA-IR) in up to 46,186 nondiabetic participants. Follow-up of 25 loci in up to 76,558 additional subjects identified 16 loci associated with fasting glucose and HOMA-B and two loci associated with fasting insulin and HOMA-IR. These include nine loci newly associated with fasting glucose (in or near ADCY5, MADD, ADRA2A, CRY2, FADS1, GLIS3, SLC2A2, PROX1 and C2CD4B) and one influencing fasting insulin and HOMA-IR (near IGF1). We also demonstrated association of ADCY5, PROX1, GCK, GCKR and DGKB-TMEM195 with type 2 diabetes. Within these loci, likely biological candidate genes influence signal transduction, cell proliferation, development, glucose-sensing and circadian regulation. Our results demonstrate that genetic studies of glycemic traits can identify type 2 diabetes risk loci, as well as loci containing gene variants that are associated with a modest elevation in glucose levels but are not associated with overt diabetes.
Keywords: Adolescent; Adult; Alleles; Blood Glucose; Child; Databases, Genetic; Diabetes Mellitus, Type 2; DNA Copy Number Variations; Fasting; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Homeostasis; Humans; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Reproducibility of Results

Novel associations of multiple genetic loci with plasma levels of factor VII, factor VIII, and von Willebrand factor: The CHARGE (Cohorts for Heart and Aging Research in Genome Epidemiology) Consortium. - Smith, Nicholas L; Chen, Ming-Huei; Dehghan, Abbas; Strachan, David P; Basu, Saonli; Soranzo, Nicole; Hayward, Caroline; Rudan, Igor; Sabater-Lleal, Maria; Bis, Joshua C; de Maat, Moniek P M; Rumley, Ann; et al. (Circulation, 2010)
BACKGROUND: Plasma levels of coagulation factors VII (FVII), VIII (FVIII), and von Willebrand factor (vWF) influence risk of hemorrhage and thrombosis. We conducted genome-wide association studies to identify new loci associated with plasma levels. METHODS AND RESULTS: The setting of the study included 5 community-based studies for discovery comprising 23 608 European-ancestry participants: Atherosclerosis Risk In Communities Study, Cardiovascular Health Study, British 1958 Birth Cohort, Framingham Heart Study, and Rotterdam Study. All subjects had genome-wide single-nucleotide polymorphism (SNP) scans and at least 1 phenotype measured: FVII activity/antigen, FVIII activity, and vWF antigen. Each study used its genotype data to impute to HapMap SNPs and independently conducted association analyses of hemostasis measures using an additive genetic model. Study findings were combined by meta-analysis. Replication was conducted in 7604 participants not in the discovery cohort. For FVII, 305 SNPs exceeded the genome-wide significance threshold of 5.0x10(-8) and comprised 5 loci on 5 chromosomes: 2p23 (smallest P value 6.2x10(-24)), 4q25 (3.6x10(-12)), 11q12 (2.0x10(-10)), 13q34 (9.0x10(-259)), and 20q11.2 (5.7x10(-37)). Loci were within or near genes, including 4 new candidate genes and F7 (13q34). For vWF, 400 SNPs exceeded the threshold and marked 8 loci on 6 chromosomes: 6q24 (1.2x10(-22)), 8p21 (1.3x10(-16)), 9q34 (<5.0x10(-324)), 12p13 (1.7x10(-32)), 12q23 (7.3x10(-10)), 12q24.3 (3.8x10(-11)), 14q32 (2.3x10(-10)), and 19p13.2 (1.3x10(-9)). All loci were within genes, including 6 new candidate genes, as well as ABO (9q34) and VWF (12p13). For FVIII, 5 loci were identified and overlapped vWF findings. Nine of the 10 new findings were replicated. CONCLUSIONS: New genetic associations were discovered outside previously known biological pathways and may point to novel prevention and treatment targets of hemostasis disorders.
Keywords: Adult; Factor VII; Factor VIII; Female; Genome-Wide Association Study; Hemostasis; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Thrombosis; von Willebrand Factor

Genetic predictors of fibrin D-dimer levels in healthy adults. - Smith, Nicholas L; Huffman, Jennifer E; Strachan, David P; Huang, Jie; Dehghan, Abbas; Trompet, Stella; Lopez, Lorna M; Shin, So-Youn; Baumert, Jens; Vitart, Veronique; Bis, Joshua C; Wild, Sarah H; et al. (Circulation, 2011)
BACKGROUND: Fibrin fragment D-dimer, one of several peptides produced when crosslinked fibrin is degraded by plasmin, is the most widely used clinical marker of activated blood coagulation. To identity genetic loci influencing D-dimer levels, we performed the first large-scale, genome-wide association search. METHODS AND RESULTS: A genome-wide investigation of the genomic correlates of plasma D-dimer levels was conducted among 21 052 European-ancestry adults. Plasma levels of D-dimer were measured independently in each of 13 cohorts. Each study analyzed the association between ≈2.6 million genotyped and imputed variants across the 22 autosomal chromosomes and natural-log–transformed D-dimer levels using linear regression in additive genetic models adjusted for age and sex. Among all variants, 74 exceeded the genome-wide significance threshold and marked 3 regions. At 1p22, rs12029080 (P=6.4×10(-52)) was 46.0 kb upstream from F3, coagulation factor III (tissue factor). At 1q24, rs6687813 (P=2.4×10(-14)) was 79.7 kb downstream of F5, coagulation factor V. At 4q32, rs13109457 (P=2.9×10(-18)) was located between 2 fibrinogen genes: 10.4 kb downstream from FGG and 3.0 kb upstream from FGA. Variants were associated with a 0.099-, 0.096-, and 0.061-unit difference, respectively, in natural-log–transformed D-dimer and together accounted for 1.8% of the total variance. When adjusted for nonsynonymous substitutions in F5 and FGA loci known to be associated with D-dimer levels, there was no evidence of an additional association at either locus. CONCLUSIONS: Three genes were associated with fibrin D-dimer levels. Of these 3, the F3 association was the strongest, and has not been previously reported.
Keywords: Adult; Aged; Blood Coagulation; European Continental Ancestry Group; Factor V; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Genetic Testing; Genome-Wide Association Study; Humans; Male; Middle Aged; Reference Values; Thromboplastin

Genetic variants in novel pathways influence blood pressure and cardiovascular disease risk. - Ehret, Georg B; Munroe, Patricia B; Rice, Kenneth M; Bochud, Murielle; Johnson, Andrew D; Chasman, Daniel I; Smith, Albert V; Tobin, Martin D; Verwoert, Germaine C; Hwang, Shih-Jen; Pihur, Vasyl; Vollenweider, Peter; et al. (Nature, 2011)
Blood pressure is a heritable trait influenced by several biological pathways and responsive to environmental stimuli. Over one billion people worldwide have hypertension (≥140 mm Hg systolic blood pressure or  ≥90 mm Hg diastolic blood pressure). Even small increments in blood pressure are associated with an increased risk of cardiovascular events. This genome-wide association study of systolic and diastolic blood pressure, which used a multi-stage design in 200,000 individuals of European descent, identified sixteen novel loci: six of these loci contain genes previously known or suspected to regulate blood pressure (GUCY1A3-GUCY1B3, NPR3-C5orf23, ADM, FURIN-FES, GOSR2, GNAS-EDN3); the other ten provide new clues to blood pressure physiology. A genetic risk score based on 29 genome-wide significant variants was associated with hypertension, left ventricular wall thickness, stroke and coronary artery disease, but not kidney disease or kidney function. We also observed associations with blood pressure in East Asian, South Asian and African ancestry individuals. Our findings provide new insights into the genetics and biology of blood pressure, and suggest potential novel therapeutic pathways for cardiovascular disease prevention.
Keywords: Africa; Asia; Blood Pressure; Cardiovascular Diseases; Coronary Artery Disease; Europe; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Kidney Diseases; Polymorphism, Single Nucleotide; Stroke

Genetic variation near IRS1 associates with reduced adiposity and an impaired metabolic profile. - Kilpeläinen, Tuomas O; Zillikens, M Carola; Stančáková, Alena; Finucane, Francis M; Ried, Janina S; Langenberg, Claudia; Zhang, Weihua; Beckmann, Jacques S; Luan, Jian'an; Vandenput, Liesbeth; Styrkarsdottir, Unnur; Zhou, Yanhua; et al. (Nat Genet, 2011)
Genome-wide association studies have identified 32 loci influencing body mass index, but this measure does not distinguish lean from fat mass. To identify adiposity loci, we meta-analyzed associations between ∼2.5 million SNPs and body fat percentage from 36,626 individuals and followed up the 14 most significant (P < 10(-6)) independent loci in 39,576 individuals. We confirmed a previously established adiposity locus in FTO (P = 3 × 10(-26)) and identified two new loci associated with body fat percentage, one near IRS1 (P = 4 × 10(-11)) and one near SPRY2 (P = 3 × 10(-8)). Both loci contain genes with potential links to adipocyte physiology. Notably, the body-fat-decreasing allele near IRS1 is associated with decreased IRS1 expression and with an impaired metabolic profile, including an increased visceral to subcutaneous fat ratio, insulin resistance, dyslipidemia, risk of diabetes and coronary artery disease and decreased adiponectin levels. Our findings provide new insights into adiposity and insulin resistance.
Keywords: Adiponectin; Adiposity; Alleles; Body Fat Distribution; Body Mass Index; Body Weight; Female; Genetic Variation; Genome-Wide Association Study; Humans; Insulin Receptor Substrate Proteins; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Meta-Analysis as Topic; Metabolome; Obesity; Polymorphism, Single Nucleotide; Subcutaneous Fat

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

Meta-analysis of genome-wide association studies in >80 000 subjects identifies multiple loci for C-reactive protein levels. - Dehghan, Abbas; Dupuis, Josée; Barbalic, Maja; Bis, Joshua C; Eiriksdottir, Gudny; Lu, Chen; Pellikka, Niina; Wallaschofski, Henri; Kettunen, Johannes; Henneman, Peter; Baumert, Jens; Strachan, David P; et al. (Circulation, 2011)
BACKGROUND: C-reactive protein (CRP) is a heritable marker of chronic inflammation that is strongly associated with cardiovascular disease. We sought to identify genetic variants that are associated with CRP levels. METHODS AND RESULTS: We performed a genome-wide association analysis of CRP in 66 185 participants from 15 population-based studies. We sought replication for the genome-wide significant and suggestive loci in a replication panel comprising 16 540 individuals from 10 independent studies. We found 18 genome-wide significant loci, and we provided evidence of replication for 8 of them. Our results confirm 7 previously known loci and introduce 11 novel loci that are implicated in pathways related to the metabolic syndrome (APOC1, HNF1A, LEPR, GCKR, HNF4A, and PTPN2) or the immune system (CRP, IL6R, NLRP3, IL1F10, and IRF1) or that reside in regions previously not known to play a role in chronic inflammation (PPP1R3B, SALL1, PABPC4, ASCL1, RORA, and BCL7B). We found a significant interaction of body mass index with LEPR (P<2.9×10(-6)). A weighted genetic risk score that was developed to summarize the effect of risk alleles was strongly associated with CRP levels and explained ≈5% of the trait variance; however, there was no evidence for these genetic variants explaining the association of CRP with coronary heart disease. CONCLUSIONS: We identified 18 loci that were associated with CRP levels. Our study highlights immune response and metabolic regulatory pathways involved in the regulation of chronic inflammation.
Keywords: Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Risk Factors; Vasculitis

New gene functions in megakaryopoiesis and platelet formation. - Gieger, Christian; Radhakrishnan, Aparna; Cvejic, Ana; Tang, Weihong; Porcu, Eleonora; Pistis, Giorgio; Serbanovic-Canic, Jovana; Elling, Ulrich; Goodall, Alison H; Labrune, Yann; Lopez, Lorna M; Mägi, Reedik; et al. (Nature, 2011)
Platelets are the second most abundant cell type in blood and are essential for maintaining haemostasis. Their count and volume are tightly controlled within narrow physiological ranges, but there is only limited understanding of the molecular processes controlling both traits. Here we carried out a high-powered meta-analysis of genome-wide association studies (GWAS) in up to 66,867 individuals of European ancestry, followed by extensive biological and functional assessment. We identified 68 genomic loci reliably associated with platelet count and volume mapping to established and putative novel regulators of megakaryopoiesis and platelet formation. These genes show megakaryocyte-specific gene expression patterns and extensive network connectivity. Using gene silencing in Danio rerio and Drosophila melanogaster, we identified 11 of the genes as novel regulators of blood cell formation. Taken together, our findings advance understanding of novel gene functions controlling fate-determining events during megakaryopoiesis and platelet formation, providing a new example of successful translation of GWAS to function.
Keywords: Animals; Blood Platelets; Cell Size; Drosophila melanogaster; Drosophila Proteins; Europe; Gene Expression Profiling; Gene Silencing; Genome, Human; Genome-Wide Association Study; Hematopoiesis; Humans; Megakaryocytes; Platelet Count; Protein Interaction Maps; Transcription, Genetic; Zebrafish; Zebrafish Proteins

Genome-wide association study for circulating levels of PAI-1 provides novel insights into its regulation. - Huang, Jie; Sabater-Lleal, Maria; Asselbergs, Folkert W; Tregouet, David; Shin, So-Youn; Ding, Jingzhong; Baumert, Jens; Oudot-Mellakh, Tiphaine; Folkersen, Lasse; Johnson, Andrew D; Smith, Nicholas L; Williams, Scott M; et al. (Blood, 2012)
We conducted a genome-wide association study to identify novel associations between genetic variants and circulating plasminogen activator inhibitor-1 (PAI-1) concentration, and examined functional implications of variants and genes that were discovered. A discovery meta-analysis was performed in 19 599 subjects, followed by replication analysis of genome-wide significant (P < 5 × 10(-8)) single nucleotide polymorphisms (SNPs) in 10 796 independent samples. We further examined associations with type 2 diabetes and coronary artery disease, assessed the functional significance of the SNPs for gene expression in human tissues, and conducted RNA-silencing experiments for one novel association. We confirmed the association of the 4G/5G proxy SNP rs2227631 in the promoter region of SERPINE1 (7q22.1) and discovered genome-wide significant associations at 3 additional loci: chromosome 7q22.1 close to SERPINE1 (rs6976053, discovery P = 3.4 × 10(-10)); chromosome 11p15.2 within ARNTL (rs6486122, discovery P = 3.0 × 10(-8)); and chromosome 3p25.2 within PPARG (rs11128603, discovery P = 2.9 × 10(-8)). Replication was achieved for the 7q22.1 and 11p15.2 loci. There was nominal association with type 2 diabetes and coronary artery disease at ARNTL (P < .05). Functional studies identified MUC3 as a candidate gene for the second association signal on 7q22.1. In summary, SNPs in SERPINE1 and ARNTL and an SNP associated with the expression of MUC3 were robustly associated with circulating levels of PAI-1.
Keywords: Adaptor Proteins, Signal Transducing; ARNTL Transcription Factors; ATPases Associated with Diverse Cellular Activities; Cell Line; Cell Line, Tumor; Cohort Studies; Coronary Artery Disease; Diabetes Mellitus, Type 2; Gene Expression Profiling; Gene Expression Regulation; Gene Frequency; Genome-Wide Association Study; Genotype; Humans; LIM Domain Proteins; Meta-Analysis as Topic; Monocytes; Mucin-3; Plasminogen Activator Inhibitor 1; Polymorphism, Single Nucleotide; PPAR gamma; Proteasome Endopeptidase Complex; RNA Interference; Transcription Factors

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Polymerase gamma; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Novel loci for adiponectin levels and their influence on type 2 diabetes and metabolic traits: a multi-ethnic meta-analysis of 45,891 individuals. - Dastani, Zari; Hivert, Marie-France; Timpson, Nicholas; Perry, John R B; Yuan, Xin; Scott, Robert A; Henneman, Peter; Heid, Iris M; Kizer, Jorge R; Lyytikäinen, Leo-Pekka; Fuchsberger, Christian; Tanaka, Toshiko; et al. (PLoS Genet, 2012)
Circulating levels of adiponectin, a hormone produced predominantly by adipocytes, are highly heritable and are inversely associated with type 2 diabetes mellitus (T2D) and other metabolic traits. We conducted a meta-analysis of genome-wide association studies in 39,883 individuals of European ancestry to identify genes associated with metabolic disease. We identified 8 novel loci associated with adiponectin levels and confirmed 2 previously reported loci (P = 4.5×10(-8)-1.2×10(-43)). Using a novel method to combine data across ethnicities (N = 4,232 African Americans, N = 1,776 Asians, and N = 29,347 Europeans), we identified two additional novel loci. Expression analyses of 436 human adipocyte samples revealed that mRNA levels of 18 genes at candidate regions were associated with adiponectin concentrations after accounting for multiple testing (p<3×10(-4)). We next developed a multi-SNP genotypic risk score to test the association of adiponectin decreasing risk alleles on metabolic traits and diseases using consortia-level meta-analytic data. This risk score was associated with increased risk of T2D (p = 4.3×10(-3), n = 22,044), increased triglycerides (p = 2.6×10(-14), n = 93,440), increased waist-to-hip ratio (p = 1.8×10(-5), n = 77,167), increased glucose two hours post oral glucose tolerance testing (p = 4.4×10(-3), n = 15,234), increased fasting insulin (p = 0.015, n = 48,238), but with lower in HDL-cholesterol concentrations (p = 4.5×10(-13), n = 96,748) and decreased BMI (p = 1.4×10(-4), n = 121,335). These findings identify novel genetic determinants of adiponectin levels, which, taken together, influence risk of T2D and markers of insulin resistance.
Keywords: Adiponectin; African Americans; Asian Continental Ancestry Group; Cholesterol, HDL; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Tolerance Test; Humans; Insulin Resistance; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Waist-Hip Ratio

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Genome-wide meta-analysis identifies 11 new loci for anthropometric traits and provides insights into genetic architecture. - Berndt, Sonja I; Gustafsson, Stefan; Mägi, Reedik; Ganna, Andrea; Wheeler, Eleanor; Feitosa, Mary F; Justice, Anne E; Monda, Keri L; Croteau-Chonka, Damien C; Day, Felix R; Esko, Tõnu; Fall, Tove; et al. (Nat Genet, 2013)
Approaches exploiting trait distribution extremes may be used to identify loci associated with common traits, but it is unknown whether these loci are generalizable to the broader population. In a genome-wide search for loci associated with the upper versus the lower 5th percentiles of body mass index, height and waist-to-hip ratio, as well as clinical classes of obesity, including up to 263,407 individuals of European ancestry, we identified 4 new loci (IGFBP4, H6PD, RSRC1 and PPP2R2A) influencing height detected in the distribution tails and 7 new loci (HNF4G, RPTOR, GNAT2, MRPS33P4, ADCY9, HS6ST3 and ZZZ3) for clinical classes of obesity. Further, we find a large overlap in genetic structure and the distribution of variants between traits based on extremes and the general population and little etiological heterogeneity between obesity subgroups.
Keywords: Anthropometry; Body Height; Body Mass Index; Case-Control Studies; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Meta-Analysis as Topic; Obesity; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Waist-Hip Ratio

Identification of heart rate-associated loci and their effects on cardiac conduction and rhythm disorders. - den Hoed, Marcel; Eijgelsheim, Mark; Esko, Tõnu; Brundel, Bianca J J M; Peal, David S; Evans, David M; Nolte, Ilja M; Segrè, Ayellet V; Holm, Hilma; Handsaker, Robert E; Westra, Harm-Jan; Johnson, Toby; et al. (Nat Genet, 2013)
Elevated resting heart rate is associated with greater risk of cardiovascular disease and mortality. In a 2-stage meta-analysis of genome-wide association studies in up to 181,171 individuals, we identified 14 new loci associated with heart rate and confirmed associations with all 7 previously established loci. Experimental downregulation of gene expression in Drosophila melanogaster and Danio rerio identified 20 genes at 11 loci that are relevant for heart rate regulation and highlight a role for genes involved in signal transmission, embryonic cardiac development and the pathophysiology of dilated cardiomyopathy, congenital heart failure and/or sudden cardiac death. In addition, genetic susceptibility to increased heart rate is associated with altered cardiac conduction and reduced risk of sick sinus syndrome, and both heart rate-increasing and heart rate-decreasing variants associate with risk of atrial fibrillation. Our findings provide fresh insights into the mechanisms regulating heart rate and identify new therapeutic targets.
Keywords: Animals; Arrhythmias, Cardiac; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Heart Rate; Humans; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Ischemic stroke is associated with the ABO locus: the EuroCLOT study. - Williams, Frances M K; Carter, Angela M; Hysi, Pirro G; Surdulescu, Gabriela; Hodgkiss, Dylan; Soranzo, Nicole; Traylor, Matthew; Bevan, Steve; Dichgans, Martin; Rothwell, Peter M W; Sudlow, Cathie; Farrall, Martin; et al. (Ann Neurol, 2013)
OBJECTIVE: End-stage coagulation and the structure/function of fibrin are implicated in the pathogenesis of ischemic stroke. We explored whether genetic variants associated with end-stage coagulation in healthy volunteers account for the genetic predisposition to ischemic stroke and examined their influence on stroke subtype. METHODS: Common genetic variants identified through genome-wide association studies of coagulation factors and fibrin structure/function in healthy twins (n = 2,100, Stage 1) were examined in ischemic stroke (n = 4,200 cases) using 2 independent samples of European ancestry (Stage 2). A third clinical collection having stroke subtyping (total 8,900 cases, 55,000 controls) was used for replication (Stage 3). RESULTS: Stage 1 identified 524 single nucleotide polymorphisms (SNPs) from 23 linkage disequilibrium blocks having significant association (p < 5 × 10(-8)) with 1 or more coagulation/fibrin phenotypes. The most striking associations included SNP rs5985 with factor XIII activity (p = 2.6 × 10(-186)), rs10665 with FVII (p = 2.4 × 10(-47)), and rs505922 in the ABO gene with both von Willebrand factor (p = 4.7 × 10(-57)) and factor VIII (p = 1.2 × 10(-36)). In Stage 2, the 23 independent SNPs were examined in stroke cases/noncases using MOnica Risk, Genetics, Archiving and Monograph (MORGAM) and Wellcome Trust Case Control Consortium 2 collections. SNP rs505922 was nominally associated with ischemic stroke (odds ratio = 0.94, 95% confidence interval = 0.88-0.99, p = 0.023). Independent replication in Meta-Stroke confirmed the rs505922 association with stroke, beta (standard error, SE) = 0.066 (0.02), p = 0.001, a finding specific to large-vessel and cardioembolic stroke (p = 0.001 and p = < 0.001, respectively) but not seen with small-vessel stroke (p = 0.811). INTERPRETATION: ABO gene variants are associated with large-vessel and cardioembolic stroke but not small-vessel disease. This work sheds light on the different pathogenic mechanisms underpinning stroke subtype.
Keywords: ABO Blood-Group System; Adolescent; Adult; Aged; Aged, 80 and over; Blood Coagulation; Brain Ischemia; Cohort Studies; Europe; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Stroke; Young Adult

A meta-analysis of thyroid-related traits reveals novel loci and gender-specific differences in the regulation of thyroid function. - Porcu, Eleonora; Medici, Marco; Pistis, Giorgio; Volpato, Claudia B; Wilson, Scott G; Cappola, Anne R; Bos, Steffan D; Deelen, Joris; den Heijer, Martin; Freathy, Rachel M; Lahti, Jari; Liu, Chunyu; et al. (PLoS Genet, 2013)
Thyroid hormone is essential for normal metabolism and development, and overt abnormalities in thyroid function lead to common endocrine disorders affecting approximately 10% of individuals over their life span. In addition, even mild alterations in thyroid function are associated with weight changes, atrial fibrillation, osteoporosis, and psychiatric disorders. To identify novel variants underlying thyroid function, we performed a large meta-analysis of genome-wide association studies for serum levels of the highly heritable thyroid function markers TSH and FT4, in up to 26,420 and 17,520 euthyroid subjects, respectively. Here we report 26 independent associations, including several novel loci for TSH (PDE10A, VEGFA, IGFBP5, NFIA, SOX9, PRDM11, FGF7, INSR, ABO, MIR1179, NRG1, MBIP, ITPK1, SASH1, GLIS3) and FT4 (LHX3, FOXE1, AADAT, NETO1/FBXO15, LPCAT2/CAPNS2). Notably, only limited overlap was detected between TSH and FT4 associated signals, in spite of the feedback regulation of their circulating levels by the hypothalamic-pituitary-thyroid axis. Five of the reported loci (PDE8B, PDE10A, MAF/LOC440389, NETO1/FBXO15, and LPCAT2/CAPNS2) show strong gender-specific differences, which offer clues for the known sexual dimorphism in thyroid function and related pathologies. Importantly, the TSH-associated loci contribute not only to variation within the normal range, but also to TSH values outside the reference range, suggesting that they may be involved in thyroid dysfunction. Overall, our findings explain, respectively, 5.64% and 2.30% of total TSH and FT4 trait variance, and they improve the current knowledge of the regulation of hypothalamic-pituitary-thyroid axis function and the consequences of genetic variation for hypo- or hyperthyroidism.
Keywords: Female; Genome-Wide Association Study; Humans; Hyperthyroidism; Hypothyroidism; Male; Phenotype; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Sex Characteristics; Signal Transduction; Thyroid Gland; Thyrotropin; Thyroxine

Multiethnic meta-analysis of genome-wide association studies in >100 000 subjects identifies 23 fibrinogen-associated Loci but no strong evidence of a causal association between circulating fibrinogen and cardiovascular disease. - Sabater-Lleal, Maria; Huang, Jie; Chasman, Daniel; Naitza, Silvia; Dehghan, Abbas; Johnson, Andrew D; Teumer, Alexander; Reiner, Alex P; Folkersen, Lasse; Basu, Saonli; Rudnicka, Alicja R; Trompet, Stella; et al. (Circulation, 2013)
BACKGROUND: Estimates of the heritability of plasma fibrinogen concentration, an established predictor of cardiovascular disease, range from 34% to 50%. Genetic variants so far identified by genome-wide association studies explain only a small proportion (<2%) of its variation. METHODS AND RESULTS: We conducted a meta-analysis of 28 genome-wide association studies including >90 000 subjects of European ancestry, the first genome-wide association meta-analysis of fibrinogen levels in 7 studies in blacks totaling 8289 samples, and a genome-wide association study in Hispanics totaling 1366 samples. Evaluation for association of single-nucleotide polymorphisms with clinical outcomes included a total of 40 695 cases and 85 582 controls for coronary artery disease, 4752 cases and 24 030 controls for stroke, and 3208 cases and 46 167 controls for venous thromboembolism. Overall, we identified 24 genome-wide significant (P<5×10(-8)) independent signals in 23 loci, including 15 novel associations, together accounting for 3.7% of plasma fibrinogen variation. Gene-set enrichment analysis highlighted key roles in fibrinogen regulation for the 3 structural fibrinogen genes and pathways related to inflammation, adipocytokines, and thyrotrophin-releasing hormone signaling. Whereas lead single-nucleotide polymorphisms in a few loci were significantly associated with coronary artery disease, the combined effect of all 24 fibrinogen-associated lead single-nucleotide polymorphisms was not significant for coronary artery disease, stroke, or venous thromboembolism. CONCLUSIONS: We identify 23 robustly associated fibrinogen loci, 15 of which are new. Clinical outcome analysis of these loci does not support a causal relationship between circulating levels of fibrinogen and coronary artery disease, stroke, or venous thromboembolism.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Cardiovascular Diseases; Coronary Artery Disease; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Hispanic Americans; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Risk Factors; Stroke; Venous Thromboembolism; Young Adult

Genome-wide association study for circulating tissue plasminogen activator levels and functional follow-up implicates endothelial STXBP5 and STX2. - Huang, Jie; Huffman, Jennifer E; Yamakuchi, Munekazu; Yamkauchi, Munekazu; Trompet, Stella; Asselbergs, Folkert W; Sabater-Lleal, Maria; Trégouët, David-Alexandre; Chen, Wei-Min; Smith, Nicholas L; Kleber, Marcus E; Shin, So-Youn; et al. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: Tissue plasminogen activator (tPA), a serine protease, catalyzes the conversion of plasminogen to plasmin, the major enzyme responsible for endogenous fibrinolysis. In some populations, elevated plasma levels of tPA have been associated with myocardial infarction and other cardiovascular diseases. We conducted a meta-analysis of genome-wide association studies to identify novel correlates of circulating levels of tPA. APPROACH AND RESULTS: Fourteen cohort studies with tPA measures (N=26 929) contributed to the meta-analysis. Three loci were significantly associated with circulating tPA levels (P<5.0×10(-8)). The first locus is on 6q24.3, with the lead single nucleotide polymorphism (SNP; rs9399599; P=2.9×10(-14)) within STXBP5. The second locus is on 8p11.21. The lead SNP (rs3136739; P=1.3×10(-9)) is intronic to POLB and <200 kb away from the tPA encoding the gene PLAT. We identified a nonsynonymous SNP (rs2020921) in modest linkage disequilibrium with rs3136739 (r(2)=0.50) within exon 5 of PLAT (P=2.0×10(-8)). The third locus is on 12q24.33, with the lead SNP (rs7301826; P=1.0×10(-9)) within intron 7 of STX2. We further found evidence for the association of lead SNPs in STXBP5 and STX2 with expression levels of the respective transcripts. In in vitro cell studies, silencing STXBP5 decreased the release of tPA from vascular endothelial cells, whereas silencing STX2 increased the tPA release. Through an in silico lookup, we found no associations of the 3 lead SNPs with coronary artery disease or stroke. CONCLUSIONS: We identified 3 loci associated with circulating tPA levels, the PLAT region, STXBP5, and STX2. Our functional studies implicate a novel role for STXBP5 and STX2 in regulating tPA release.
Keywords: Aged; Cells, Cultured; Coronary Artery Disease; Endothelial Cells; Europe; Female; Gene Expression Regulation; Gene Silencing; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; R-SNARE Proteins; Risk Factors; Stroke; Syntaxin 1; Tissue Plasminogen Activator; Transfection; United States; Up-Regulation

Identification of novel genetic Loci associated with thyroid peroxidase antibodies and clinical thyroid disease. - Medici, Marco; Porcu, Eleonora; Pistis, Giorgio; Teumer, Alexander; Brown, Suzanne J; Jensen, Richard A; Rawal, Rajesh; Roef, Greet L; Plantinga, Theo S; Vermeulen, Sita H; Lahti, Jari; Simmonds, Matthew J; et al. (PLoS Genet, 2014)
Autoimmune thyroid diseases (AITD) are common, affecting 2-5% of the general population. Individuals with positive thyroid peroxidase antibodies (TPOAbs) have an increased risk of autoimmune hypothyroidism (Hashimoto's thyroiditis), as well as autoimmune hyperthyroidism (Graves' disease). As the possible causative genes of TPOAbs and AITD remain largely unknown, we performed GWAS meta-analyses in 18,297 individuals for TPOAb-positivity (1769 TPOAb-positives and 16,528 TPOAb-negatives) and in 12,353 individuals for TPOAb serum levels, with replication in 8,990 individuals. Significant associations (P<5×10(-8)) were detected at TPO-rs11675434, ATXN2-rs653178, and BACH2-rs10944479 for TPOAb-positivity, and at TPO-rs11675434, MAGI3-rs1230666, and KALRN-rs2010099 for TPOAb levels. Individual and combined effects (genetic risk scores) of these variants on (subclinical) hypo- and hyperthyroidism, goiter and thyroid cancer were studied. Individuals with a high genetic risk score had, besides an increased risk of TPOAb-positivity (OR: 2.18, 95% CI 1.68-2.81, P = 8.1×10(-8)), a higher risk of increased thyroid-stimulating hormone levels (OR: 1.51, 95% CI 1.26-1.82, P = 2.9×10(-6)), as well as a decreased risk of goiter (OR: 0.77, 95% CI 0.66-0.89, P = 6.5×10(-4)). The MAGI3 and BACH2 variants were associated with an increased risk of hyperthyroidism, which was replicated in an independent cohort of patients with Graves' disease (OR: 1.37, 95% CI 1.22-1.54, P = 1.2×10(-7) and OR: 1.25, 95% CI 1.12-1.39, P = 6.2×10(-5)). The MAGI3 variant was also associated with an increased risk of hypothyroidism (OR: 1.57, 95% CI 1.18-2.10, P = 1.9×10(-3)). This first GWAS meta-analysis for TPOAbs identified five newly associated loci, three of which were also associated with clinical thyroid disease. With these markers we identified a large subgroup in the general population with a substantially increased risk of TPOAbs. The results provide insight into why individuals with thyroid autoimmunity do or do not eventually develop thyroid disease, and these markers may therefore predict which TPOAb-positives are particularly at risk of developing clinical thyroid dysfunction.
Keywords: Autoantibodies; Genetic Loci; Genome-Wide Association Study; Graves Disease; Hashimoto Disease; Humans; Iodide Peroxidase; Risk Factors; Thyroiditis, Autoimmune; Thyrotropin

Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: African Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide

SOS2 and ACP1 Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2016)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (nStage1: 111,666; nStage2: 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (PPM1J, EDEM3, ACP1, SPEG, EYA4, CYP1A1, and ATXN2L; PStage1<3.7×10(-7)), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, SOS2 (P=5.4×10(-8) by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of acp1- and sos2-knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.

Whole-Exome Sequencing Identifies Loci Associated with Blood Cell Traits and Reveals a Role for Alternative GFI1B Splice Variants in Human Hematopoiesis. - Polfus, Linda M; Khajuria, Rajiv K; Schick, Ursula M; Pankratz, Nathan; Pazoki, Raha; Brody, Jennifer A; Chen, Ming-Huei; Auer, Paul L; Floyd, James S; Huang, Jie; Lange, Leslie; van Rooij, Frank J A; et al. (Am J Hum Genet, 2016)

Association Between Telomere Length and Risk of Cancer and Non-Neoplastic Diseases: A Mendelian Randomization Study. - Haycock, Philip C; Burgess, Stephen; Nounu, Aayah; Zheng, Jie; Okoli, George N; Bowden, Jack; Wade, Kaitlin Hazel; Timpson, Nicholas J; Evans, David M; Willeit, Peter; Aviv, Abraham; Gaunt, Tom R; et al. (JAMA Oncol, 2017)
Importance: The causal direction and magnitude of the association between telomere length and incidence of cancer and non-neoplastic diseases is uncertain owing to the susceptibility of observational studies to confounding and reverse causation. Objective: To conduct a Mendelian randomization study, using germline genetic variants as instrumental variables, to appraise the causal relevance of telomere length for risk of cancer and non-neoplastic diseases. Data Sources: Genomewide association studies (GWAS) published up to January 15, 2015. Study Selection: GWAS of noncommunicable diseases that assayed germline genetic variation and did not select cohort or control participants on the basis of preexisting diseases. Of 163 GWAS of noncommunicable diseases identified, summary data from 103 were available. Data Extraction and Synthesis: Summary association statistics for single nucleotide polymorphisms (SNPs) that are strongly associated with telomere length in the general population. Main Outcomes and Measures: Odds ratios (ORs) and 95% confidence intervals (CIs) for disease per standard deviation (SD) higher telomere length due to germline genetic variation. Results: Summary data were available for 35 cancers and 48 non-neoplastic diseases, corresponding to 420 081 cases (median cases, 2526 per disease) and 1 093 105 controls (median, 6789 per disease). Increased telomere length due to germline genetic variation was generally associated with increased risk for site-specific cancers. The strongest associations (ORs [95% CIs] per 1-SD change in genetically increased telomere length) were observed for glioma, 5.27 (3.15-8.81); serous low-malignant-potential ovarian cancer, 4.35 (2.39-7.94); lung adenocarcinoma, 3.19 (2.40-4.22); neuroblastoma, 2.98 (1.92-4.62); bladder cancer, 2.19 (1.32-3.66); melanoma, 1.87 (1.55-2.26); testicular cancer, 1.76 (1.02-3.04); kidney cancer, 1.55 (1.08-2.23); and endometrial cancer, 1.31 (1.07-1.61). Associations were stronger for rarer cancers and at tissue sites with lower rates of stem cell division. There was generally little evidence of association between genetically increased telomere length and risk of psychiatric, autoimmune, inflammatory, diabetic, and other non-neoplastic diseases, except for coronary heart disease (OR, 0.78 [95% CI, 0.67-0.90]), abdominal aortic aneurysm (OR, 0.63 [95% CI, 0.49-0.81]), celiac disease (OR, 0.42 [95% CI, 0.28-0.61]) and interstitial lung disease (OR, 0.09 [95% CI, 0.05-0.15]). Conclusions and Relevance: It is likely that longer telomeres increase risk for several cancers but reduce risk for some non-neoplastic diseases, including cardiovascular diseases.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Germ-Line Mutation; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Neoplasms; Polymorphism, Single Nucleotide; Risk Assessment; Telomere; Telomere Homeostasis

Impact of common genetic determinants of Hemoglobin A1c on type 2 diabetes risk and diagnosis in ancestrally diverse populations: A transethnic genome-wide meta-analysis. - Wheeler, Eleanor; Leong, Aaron; Liu, Ching-Ti; Hivert, Marie-France; Strawbridge, Rona J; Podmore, Clara; Li, Man; Yao, Jie; Sim, Xueling; Hong, Jaeyoung; Chu, Audrey Y; Zhang, Weihua; et al. (PLoS Med, 2017)
BACKGROUND: Glycated hemoglobin (HbA1c) is used to diagnose type 2 diabetes (T2D) and assess glycemic control in patients with diabetes. Previous genome-wide association studies (GWAS) have identified 18 HbA1c-associated genetic variants. These variants proved to be classifiable by their likely biological action as erythrocytic (also associated with erythrocyte traits) or glycemic (associated with other glucose-related traits). In this study, we tested the hypotheses that, in a very large scale GWAS, we would identify more genetic variants associated with HbA1c and that HbA1c variants implicated in erythrocytic biology would affect the diagnostic accuracy of HbA1c. We therefore expanded the number of HbA1c-associated loci and tested the effect of genetic risk-scores comprised of erythrocytic or glycemic variants on incident diabetes prediction and on prevalent diabetes screening performance. Throughout this multiancestry study, we kept a focus on interancestry differences in HbA1c genetics performance that might influence race-ancestry differences in health outcomes. METHODS & FINDINGS: Using genome-wide association meta-analyses in up to 159,940 individuals from 82 cohorts of European, African, East Asian, and South Asian ancestry, we identified 60 common genetic variants associated with HbA1c. We classified variants as implicated in glycemic, erythrocytic, or unclassified biology and tested whether additive genetic scores of erythrocytic variants (GS-E) or glycemic variants (GS-G) were associated with higher T2D incidence in multiethnic longitudinal cohorts (N = 33,241). Nineteen glycemic and 22 erythrocytic variants were associated with HbA1c at genome-wide significance. GS-G was associated with higher T2D risk (incidence OR = 1.05, 95% CI 1.04-1.06, per HbA1c-raising allele, p = 3 × 10-29); whereas GS-E was not (OR = 1.00, 95% CI 0.99-1.01, p = 0.60). In Europeans and Asians, erythrocytic variants in aggregate had only modest effects on the diagnostic accuracy of HbA1c. Yet, in African Americans, the X-linked G6PD G202A variant (T-allele frequency 11%) was associated with an absolute decrease in HbA1c of 0.81%-units (95% CI 0.66-0.96) per allele in hemizygous men, and 0.68%-units (95% CI 0.38-0.97) in homozygous women. The G6PD variant may cause approximately 2% (N = 0.65 million, 95% CI 0.55-0.74) of African American adults with T2D to remain undiagnosed when screened with HbA1c. Limitations include the smaller sample sizes for non-European ancestries and the inability to classify approximately one-third of the variants. Further studies in large multiethnic cohorts with HbA1c, glycemic, and erythrocytic traits are required to better determine the biological action of the unclassified variants. CONCLUSIONS: As G6PD deficiency can be clinically silent until illness strikes, we recommend investigation of the possible benefits of screening for the G6PD genotype along with using HbA1c to diagnose T2D in populations of African ancestry or groups where G6PD deficiency is common. Screening with direct glucose measurements, or genetically-informed HbA1c diagnostic thresholds in people with G6PD deficiency, may be required to avoid missed or delayed diagnoses.
Keywords: Diabetes Mellitus, Type 2; Genetic Variation; Genome-Wide Association Study; Glycated Hemoglobin A; Humans; Phenotype; Risk

Large meta-analysis of genome-wide association studies identifies five loci for lean body mass. - Zillikens, M Carola; Demissie, Serkalem; Hsu, Yi-Hsiang; Yerges-Armstrong, Laura M; Chou, Wen-Chi; Stolk, Lisette; Livshits, Gregory; Broer, Linda; Johnson, Toby; Koller, Daniel L; Kutalik, Zoltán; Luan, Jian'an; et al. (Nat Commun, 2017)
Lean body mass, consisting mostly of skeletal muscle, is important for healthy aging. We performed a genome-wide association study for whole body (20 cohorts of European ancestry with n = 38,292) and appendicular (arms and legs) lean body mass (n = 28,330) measured using dual energy X-ray absorptiometry or bioelectrical impedance analysis, adjusted for sex, age, height, and fat mass. Twenty-one single-nucleotide polymorphisms were significantly associated with lean body mass either genome wide (p < 5 × 10-8) or suggestively genome wide (p < 2.3 × 10-6). Replication in 63,475 (47,227 of European ancestry) individuals from 33 cohorts for whole body lean body mass and in 45,090 (42,360 of European ancestry) subjects from 25 cohorts for appendicular lean body mass was successful for five single-nucleotide polymorphisms in/near HSD17B11, VCAN, ADAMTSL3, IRS1, and FTO for total lean body mass and for three single-nucleotide polymorphisms in/near VCAN, ADAMTSL3, and IRS1 for appendicular lean body mass. Our findings provide new insight into the genetics of lean body mass.Lean body mass is a highly heritable trait and is associated with various health conditions. Here, Kiel and colleagues perform a meta-analysis of genome-wide association studies for whole body lean body mass and find five novel genetic loci to be significantly associated.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide analyses identify a role for SLC17A4 and AADAT in thyroid hormone regulation. - Teumer, Alexander; Chaker, Layal; Groeneweg, Stefan; Li, Yong; Di Munno, Celia; Barbieri, Caterina; Schultheiss, Ulla T; Traglia, Michela; Ahluwalia, Tarunveer S; Akiyama, Masato; Appel, Emil Vincent R; Arking, Dan E; et al. (Nat Commun, 2018)
Thyroid dysfunction is an important public health problem, which affects 10% of the general population and increases the risk of cardiovascular morbidity and mortality. Many aspects of thyroid hormone regulation have only partly been elucidated, including its transport, metabolism, and genetic determinants. Here we report a large meta-analysis of genome-wide association studies for thyroid function and dysfunction, testing 8 million genetic variants in up to 72,167 individuals. One-hundred-and-nine independent genetic variants are associated with these traits. A genetic risk score, calculated to assess their combined effects on clinical end points, shows significant associations with increased risk of both overt (Graves' disease) and subclinical thyroid disease, as well as clinical complications. By functional follow-up on selected signals, we identify a novel thyroid hormone transporter (SLC17A4) and a metabolizing enzyme (AADAT). Together, these results provide new knowledge about thyroid hormone physiology and disease, opening new possibilities for therapeutic targets.

Refining the accuracy of validated target identification through coding variant fine-mapping in type 2 diabetes. - Mahajan, Anubha; Wessel, Jennifer; Willems, Sara M; Zhao, Wei; Robertson, Neil R; Chu, Audrey Y; Gan, Wei; Kitajima, Hidetoshi; Taliun, Daniel; Rayner, N William; Guo, Xiuqing; Lu, Yingchang; et al. (Nat Genet, 2018)
We aggregated coding variant data for 81,412 type 2 diabetes cases and 370,832 controls of diverse ancestry, identifying 40 coding variant association signals (P < 2.2 × 10); of these, 16 map outside known risk-associated loci. We make two important observations. First, only five of these signals are driven by low-frequency variants: even for these, effect sizes are modest (odds ratio ≤1.29). Second, when we used large-scale genome-wide association data to fine-map the associated variants in their regional context, accounting for the global enrichment of complex trait associations in coding sequence, compelling evidence for coding variant causality was obtained for only 16 signals. At 13 others, the associated coding variants clearly represent 'false leads' with potential to generate erroneous mechanistic inference. Coding variant associations offer a direct route to biological insight for complex diseases and identification of validated therapeutic targets; however, appropriate mechanistic inference requires careful specification of their causal contribution to disease predisposition.

A catalog of genetic loci associated with kidney function from analyses of a million individuals. - Wuttke, Matthias; Li, Yong; Li, Man; Sieber, Karsten B; Feitosa, Mary F; Gorski, Mathias; Tin, Adrienne; Wang, Lihua; Chu, Audrey Y; Hoppmann, Anselm; Kirsten, Holger; Giri, Ayush; et al. (Nat Genet, 2019)
Chronic kidney disease (CKD) is responsible for a public health burden with multi-systemic complications. Through trans-ancestry meta-analysis of genome-wide association studies of estimated glomerular filtration rate (eGFR) and independent replication (n = 1,046,070), we identified 264 associated loci (166 new). Of these, 147 were likely to be relevant for kidney function on the basis of associations with the alternative kidney function marker blood urea nitrogen (n = 416,178). Pathway and enrichment analyses, including mouse models with renal phenotypes, support the kidney as the main target organ. A genetic risk score for lower eGFR was associated with clinically diagnosed CKD in 452,264 independent individuals. Colocalization analyses of associations with eGFR among 783,978 European-ancestry individuals and gene expression across 46 human tissues, including tubulo-interstitial and glomerular kidney compartments, identified 17 genes differentially expressed in kidney. Fine-mapping highlighted missense driver variants in 11 genes and kidney-specific regulatory variants. These results provide a comprehensive priority list of molecular targets for translational research.
Keywords: Chromosome Mapping; European Continental Ancestry Group; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inheritance Patterns; Kidney Function Tests; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Renal Insufficiency, Chronic; Uromodulin

Disentangling the genetics of lean mass. - Karasik, David; Zillikens, M Carola; Hsu, Yi-Hsiang; Aghdassi, Ali; Åkesson, Kristina; Amin, Najaf; Barroso, Inês; Bennett, David A; Bertram, Lars; Bochud, Murielle; Borecki, Ingrid B; Broer, Linda; et al. (Am J Clin Nutr, 2019)
Background: Lean body mass (LM) plays an important role in mobility and metabolic function. We previously identified five loci associated with LM adjusted for fat mass in kilograms. Such an adjustment may reduce the power to identify genetic signals having an association with both lean mass and fat mass. Objectives: To determine the impact of different fat mass adjustments on genetic architecture of LM and identify additional LM loci. Methods: We performed genome-wide association analyses for whole-body LM (20 cohorts of European ancestry with n = 38,292) measured using dual-energy X-ray absorptiometry) or bioelectrical impedance analysis, adjusted for sex, age, age2, and height with or without fat mass adjustments (Model 1 no fat adjustment; Model 2 adjustment for fat mass as a percentage of body mass; Model 3 adjustment for fat mass in kilograms). Results: Seven single-nucleotide polymorphisms (SNPs) in separate loci, including one novel LM locus (TNRC6B), were successfully replicated in an additional 47,227 individuals from 29 cohorts. Based on the strengths of the associations in Model 1 vs Model 3, we divided the LM loci into those with an effect on both lean mass and fat mass in the same direction and refer to those as "sumo wrestler" loci (FTO and MC4R). In contrast, loci with an impact specifically on LM were termed "body builder" loci (VCAN and ADAMTSL3). Using existing available genome-wide association study databases, LM increasing alleles of SNPs in sumo wrestler loci were associated with an adverse metabolic profile, whereas LM increasing alleles of SNPs in "body builder" loci were associated with metabolic protection. Conclusions: In conclusion, we identified one novel LM locus (TNRC6B). Our results suggest that a genetically determined increase in lean mass might exert either harmful or protective effects on metabolic traits, depending on its relation to fat mass.

The Polygenic and Monogenic Basis of Blood Traits and Diseases. - Vuckovic, Dragana; Bao, Erik L; Akbari, Parsa; Lareau, Caleb A; Mousas, Abdou; Jiang, Tao; Chen, Ming-Huei; Raffield, Laura M; Tardaguila, Manuel; Huffman, Jennifer E; Ritchie, Scott C; Megy, Karyn; et al. (Cell, 2020)
Blood cells play essential roles in human health, underpinning physiological processes such as immunity, oxygen transport, and clotting, which when perturbed cause a significant global health burden. Here we integrate data from UK Biobank and a large-scale international collaborative effort, including data for 563,085 European ancestry participants, and discover 5,106 new genetic variants independently associated with 29 blood cell phenotypes covering a range of variation impacting hematopoiesis. We holistically characterize the genetic architecture of hematopoiesis, assess the relevance of the omnigenic model to blood cell phenotypes, delineate relevant hematopoietic cell states influenced by regulatory genetic variants and gene networks, identify novel splice-altering variants mediating the associations, and assess the polygenic prediction potential for blood traits and clinical disorders at the interface of complex and Mendelian genetics. These results show the power of large-scale blood cell trait GWAS to interrogate clinically meaningful variants across a wide allelic spectrum of human variation.

Trans-ethnic and Ancestry-Specific Blood-Cell Genetics in 746,667 Individuals from 5 Global Populations. - Chen, Ming-Huei; Raffield, Laura M; Mousas, Abdou; Sakaue, Saori; Huffman, Jennifer E; Moscati, Arden; Trivedi, Bhavi; Jiang, Tao; Akbari, Parsa; Vuckovic, Dragana; Bao, Erik L; Zhong, Xue; et al. (Cell, 2020)
Most loci identified by GWASs have been found in populations of European ancestry (EUR). In trans-ethnic meta-analyses for 15 hematological traits in 746,667 participants, including 184,535 non-EUR individuals, we identified 5,552 trait-variant associations at p < 5 × 10, including 71 novel associations not found in EUR populations. We also identified 28 additional novel variants in ancestry-specific, non-EUR meta-analyses, including an IL7 missense variant in South Asians associated with lymphocyte count in vivo and IL-7 secretion levels in vitro. Fine-mapping prioritized variants annotated as functional and generated 95% credible sets that were 30% smaller when using the trans-ethnic as opposed to the EUR-only results. We explored the clinical significance and predictive value of trans-ethnic variants in multiple populations and compared genetic architecture and the effect of natural selection on these blood phenotypes between populations. Altogether, our results for hematological traits highlight the value of a more global representation of populations in genetic studies.

Whole-genome sequencing association analysis of quantitative red blood cell phenotypes: The NHLBI TOPMed program. - Hu, Yao; Stilp, Adrienne M; McHugh, Caitlin P; Rao, Shuquan; Jain, Deepti; Zheng, Xiuwen; Lane, John; Méric de Bellefon, Sébastian; Raffield, Laura M; Chen, Ming-Huei; Yanek, Lisa R; Wheeler, Marsha; et al. (Am J Hum Genet, 2021)
Whole-genome sequencing (WGS), a powerful tool for detecting novel coding and non-coding disease-causing variants, has largely been applied to clinical diagnosis of inherited disorders. Here we leveraged WGS data in up to 62,653 ethnically diverse participants from the NHLBI Trans-Omics for Precision Medicine (TOPMed) program and assessed statistical association of variants with seven red blood cell (RBC) quantitative traits. We discovered 14 single variant-RBC trait associations at 12 genomic loci, which have not been reported previously. Several of the RBC trait-variant associations (RPN1, ELL2, MIDN, HBB, HBA1, PIEZO1, and G6PD) were replicated in independent GWAS datasets imputed to the TOPMed reference panel. Most of these discovered variants are rare/low frequency, and several are observed disproportionately among non-European Ancestry (African, Hispanic/Latino, or East Asian) populations. We identified a 3 bp indel p.Lys2169del (g.88717175_88717177TCT[4]) (common only in the Ashkenazi Jewish population) of PIEZO1, a gene responsible for the Mendelian red cell disorder hereditary xerocytosis (MIM: 194380), associated with higher mean corpuscular hemoglobin concentration (MCHC). In stepwise conditional analysis and in gene-based rare variant aggregated association analysis, we identified several of the variants in HBB, HBA1, TMPRSS6, and G6PD that represent the carrier state for known coding, promoter, or splice site loss-of-function variants that cause inherited RBC disorders. Finally, we applied base and nuclease editing to demonstrate that the sentinel variant rs112097551 (nearest gene RPN1) acts through a cis-regulatory element that exerts long-range control of the gene RUVBL1 which is essential for hematopoiesis. Together, these results demonstrate the utility of WGS in ethnically diverse population-based samples and gene editing for expanding knowledge of the genetic architecture of quantitative hematologic traits and suggest a continuum between complex trait and Mendelian red cell disorders.
Keywords: Adult; Aged; Chromosomes, Human, Pair 16; Datasets as Topic; Erythrocytes; Female; Gene Editing; Genetic Variation; Genome-Wide Association Study; HEK293 Cells; Humans; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Quality Control; Reproducibility of Results; United States

Whole-genome sequencing in diverse subjects identifies genetic correlates of leukocyte traits: The NHLBI TOPMed program. - Mikhaylova, Anna V; McHugh, Caitlin P; Polfus, Linda M; Raffield, Laura M; Boorgula, Meher Preethi; Blackwell, Thomas W; Brody, Jennifer A; Broome, Jai; Chami, Nathalie; Chen, Ming-Huei; Conomos, Matthew P; Cox, Corey; et al. (Am J Hum Genet, 2021)
Many common and rare variants associated with hematologic traits have been discovered through imputation on large-scale reference panels. However, the majority of genome-wide association studies (GWASs) have been conducted in Europeans, and determining causal variants has proved challenging. We performed a GWAS of total leukocyte, neutrophil, lymphocyte, monocyte, eosinophil, and basophil counts generated from 109,563,748 variants in the autosomes and the X chromosome in the Trans-Omics for Precision Medicine (TOPMed) program, which included data from 61,802 individuals of diverse ancestry. We discovered and replicated 7 leukocyte trait associations, including (1) the association between a chromosome X, pseudo-autosomal region (PAR), noncoding variant located between cytokine receptor genes (CSF2RA and CLRF2) and lower eosinophil count; and (2) associations between single variants found predominantly among African Americans at the S1PR3 (9q22.1) and HBB (11p15.4) loci and monocyte and lymphocyte counts, respectively. We further provide evidence indicating that the newly discovered eosinophil-lowering chromosome X PAR variant might be associated with reduced susceptibility to common allergic diseases such as atopic dermatitis and asthma. Additionally, we found a burden of very rare FLT3 (13q12.2) variants associated with monocyte counts. Together, these results emphasize the utility of whole-genome sequencing in diverse samples in identifying associations missed by European-ancestry-driven GWASs.
Keywords: Asthma; Biomarkers; Dermatitis, Atopic; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Leukocytes; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Polymorphism, Single Nucleotide; Prognosis; Proteome; Pulmonary Disease, Chronic Obstructive; Quantitative Trait Loci; United Kingdom; United States; Whole Genome Sequencing